EVALUASI POSTUR KERJA OPERATOR PENGGILINGAN KELAPA BERBASIS METODE WORKPLACE ERGONOMIC RISK ASSESMENT DAN JOB STRAIN INDEX - Hidayatullah, Iqbal Fikri; Mahbubah, Nina Aini; Hidayat, Hidayat (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2021)
Home-industry is a job that depend on human labor. Coconut milling is a home-service which is depend on manual material handling through production process services. Early result based on Nordic Body Map questionnaire (NBM) exposed that coconut milling operators had skeletal muscle complaints, so an ergonomic risk evaluation was needed to prevent skeletal muscle disorders. The purpose of this study is to evaluate ergonomic risk in order to prevent coconut milling operators from being affected by musculoskeletal disorders. Workplace Ergonomic Risk Assessment (WERA) and Job Strain Index (JSI) are ergonomic approaches that are used based on the risk of repetitive motion, vibration strength, contact stress and task duration involving five main areas of the body, namely shoulders, wrists, back, neck and legs which can cause Musculoskeletal Disorders. The results showed an improvement in working posture which initially had a WERA value of 44 for operator 1 and 45 for operator 2, then improved to 27 at the low level. Furthermore, the improvement of working posture in the neck should be in a position of 10°-20° at medium level and moderate movement with multiplied pause activities. Conditions for improving work activities at the JSI value of 9 for operator 1 and 20 for operator 2 were then improved to 4.5. Improved working posture, namely in operator 1's wrist which is too bent, it is recommended for operator 1's wrist not to form an angle of less than 15° to reduce the risk.